Clinical trial on the effect of regular tea drinking on iron accumulation in genetic haemochromatosis. Issue 5 (1st November 1998) - Kaltwasser, J P; Werner, E; Schalk, K; Hansen, C; Gottschalk, R; Seidl, C
Abstract : Background —Black tea is known to be a potent inhibitor of intestinal absorption of non-haem iron at least in healthy subjects. Aims —To investigate this effect in patients with genetic haemochromatosis, and, more importantly, the effect of regular tea drinking on the accumulation of storage iron in these patients over one year. Patients —Investigations were carried out on 18 patients with clinically proven genetic haemochromatosis. For the study of storage iron accumulation, they were separated into a group instructed to drink a particularly tannin rich tea regularly with meals and a control group. Methods —Intestinal iron absorption from a test meal was measured using whole body counting. Body iron stores were evaluated quantitatively by exhaustive phlebotomy, using haemoglobin, saturation of serum iron binding capacity, and serum ferritin for the assessment of body iron status. Results —A significant reduction in iron absorption was observed when the test meal was accompanied by drinks of tea instead of water. In the tea drinking group, the increase in storage iron was reduced by about one third compared with that of the control group. Conclusions —Regular tea drinking with meals reduces the frequency of phlebotomies required in the management of patients with haemochromatosis.